PERBEDAAN EFEKTIFITAS EKSTRAK TEMULAWAK (Curcuma Xanthorrizae Roxb) DENGAN BERBAGAI KONSENTRASI TERHADAP PERTUMBUHAN CANDIDA ALBICANS PADA PLAT RESIN AKRILIK KURING PANAS - In Vitro - Inanda Nita; Musri Amurwaningsih; Uswatun N.A. Darjono (Faculty of Dentistry, Universitas Islam Sultan Agung, 2014)
Background: Temulawak (curcuma xanthorrizae roxb) contains many substance such as xanthorrizol, curcumin, essential oil, flavonoid. Essential oil and flavonoid works by damaging the cell wall and protein denaturation can inhibits the growth of the fungi Candida albicans attached to the surface of the heat cured acrylic resin plate. The purpose of this study is to determine the extract Temulawak effect on the growth of Candida albicans at heat cured acrylic resin plate. Method : The Eksperiment is true experimental laboratories with post test only controlled group design. 10x10x2 mm Acrylic resin plate was soaked into Candida albicans suspension for 48 hours at 37o then soaked in curcuma xanthorrizae roxb extract 90%, 80%, 70%, 60%, control group positive (chlorhexidine 0,2%), control negatif (water) for 8 hours at 37o. Result: The result of the experiment showed that control group (-)has the highest value (839,20 x 101 CFU/ml), while the least was 90% ekstract of curcuma xanthorrizae roxb group (23,40 x 101 CFU/ml). After normality and homogenity test was done, One Way Anova test was executed (p = 0,000. means p < 0,05). Conclussion: extract Temulawak can inhibit Candida albicans growth on heat cured acrylic resin.